Changes of level of physical fitness of handball players of 13-14 years old under the influence of acrobatic exercises and exercises with application of coordination ladder - Svetlana Chervona; Helena Biykova; Irina Pomeschikova (Kharkiv State Academy of Physical Culture, 2016)
Purpose: to develop sets of exercises for the improvement of physical training of handball players of 13-14 years old with use of acrobatic exercises and exercises with application of coordination ladder and to check their efficiency experimentally. Material & Methods: two groups of handball players of 13-14 years old of Kharkov and Ternovka of the Dnepropetrovsk region participated in the research. The following methods were used in work: analysis of scientific and methodical literature, pedagogical testing, pedagogical experiment, methods of mathematical data processing. Results: the level of physical fitness of handball players of 13-14 years old and its change under the influence of specially-selected sets of exercises are determined. Conclusions: the received reliable positive changes of coordination preparedness, separate manifestations of speed, flexibility and high-speed and power abilities of boys allow recommending the inclusion of acrobatic exercises and exercises with application of coordination ladder in the educational-training process of handball players of 13-14 years old.